Laparoscopic liver resection versus radiofrequency ablation for hepatocellular carcinoma within Milan criteria: a meta-analysis and systematic review - Xu, Lin; Lin, Zhenyu; Chen, Dong; Huang, Zhangkan (Frontiers in Oncology, 2024)
BackgroundMinimally invasive techniques have significantly gained popularity for hepatocellular carcinoma (HCC) based on the Milan criteria. However, whether or not laparoscopic liver resection (LLR) or radiofrequency ablation (RFA) is a better treatment option remains debatable. We conducted a meta-analysis to review the published data comparing LLR and RFA for HCC through Milan criteria depending on tumor recurrence risk and survival.MethodsPubMed, OvidSP, Web of Science, and Cochrane Library databases were searched from inception to December 31, 2023. The studies comparing the outcomes and methods between LLR and RFA for HCC within the Milan criteria were included.ResultsWe recruited 19 cohort studies with 2532 patients. The postoperative complication rate was low, and hospital stays were shorter in the RFA group than in the LLR group. The total tumor recurrence, the local tumor recurrence rate, and the intrahepatic tumor recurrence rate were lower within the LLR group than in the RFA group. There was no significant difference in the extrahepatic recurrence rate between the two groups. Moreover, no significant differences were observed between the groups concerning 1-, 3-, and 5-year overall survival (OS) and 1-year recurrence-free survival (RFS). However, 3-year and 5-year RFS were better within the LLR group than among the RFA group.ConclusionsThe treatment of HCC within the Milan criteria is moving toward multidisciplinary and minimally invasive approaches. Our meta-analysis identified a lower postoperative complication rate and higher recurrence rate for RFA than LLR. RFA could be an alternative treatment due to its comparable long-term efficacy with LLR.